A Glance at the Book: Metaethics Written by Simon Kirchin and a Word on its Translation - Mohammad Zandi; Moslem Ghorban Babaei; Abdollah Mottaghizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book Metaethics written by Simon Kirchin is one a book on metaethics, first published by the Palgrave Macmillan institute in 2012. Kirchin was a faculty member at the University of Kent, England, who wrote an introductory textbook on metaethics covering the most important topics in this field. Positive features of the book include the author's relatively fluent writing, detailed layout with simple and appropriate language, and raising the newest perspectives on metaethics. In contrast, failing to address some of the important points and briefly mentioning are considered its drawbacks. Considering the positive aspects of the book, as well as the major section of its discussions in Farsi, as well as the remarkable shortage of Persian resources in the field of metaethics indicate the necessity and importance of translating the book, and the authors of this article translated it based on such necessity. The difficulty of translation took extra energy from translators, in particular in translating new unprecedented book topics into Farsi, especially finding the equivalents of some terms that should be done with accuracy.